Social Class, Ingroup–Outgroup Comparison, and Citizen Evaluations: Is User Satisfaction Linked to Outcome Disparities?. Issue 2 (February 2020) - Song, Miyeon; Kim, Minjung; Favero, Nathan
Research on citizen satisfaction has emphasized the role of service quality (including expectations for quality) in shaping citizens' evaluations of public services. This article considers an understudied but important aspect of public service delivery—equity—and investigates how disparities in service outcomes between disadvantaged and advantaged groups affect citizens' evaluations of service providers. This study also examines whether citizens with different socioeconomic status (SES) have different perceptions toward the outcome disparities. Using individual-level data from secondary schools, we find that service users appear to recognize and care about a performance gap among social strata. Even when a student's individual outcome is held constant, satisfaction varies with the school-level performance gap between high-SES and low-SES students. This finding suggests that service users are concerned about not just their outcomes but also the relative positioning of outcomes for those of their own social group compared with other groups.